PELAYANAN PROGRAM JAMINAN KESEHATAN MASYARAKAT (JAMKESMAS) DI RUMAH SAKIT UMUM DAERAH KABUPATEN SEKADAU - Maria Bernadeta Damai E.01108039 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Community Health Insurance Services (JAMKESMAS) is a form of social assistance spending for health care for the poor and can not afford. The program is organized nationally to enable the cross-subsidies in order to achieve comprehensive health care for the poor. The General Hospital District of Sekadau is serving patients Jamkesmas for medical treatment. This study aims to determine the health care provided to inpatients Jamkesmas participants at the General Hospital District Sekadau. The method is a method of qualitative research. The study's findings : 1). Patients Jamkesmas card users are not satisfied with the services provided by medical personnel, officers generally are not quick in providing health care to patients Jamkesmas participants.2). Patients who indicated Jamkesmas card compounded the administrative paperwork such as service is slow so it takes a long time. 3). The services provided have not been up / not good due to the attitudes and behavior of officers who seemed to slow in providing services. This fact requires for the General Hospital District of Sekadau must provide quality service and quality to patients on Community Health Insurance card.Key word : Health Services, JAMKESMAS Program, Transparency of service, Accountability, Participatory.